2017
DOI: 10.1016/j.jaad.2016.11.041
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of guselkumab, an anti-interleukin-23 monoclonal antibody, compared with adalimumab for the continuous treatment of patients with moderate to severe psoriasis: Results from the phase III, double-blinded, placebo- and active comparator–controlled VOYAGE 1 trial

Abstract: Guselkumab demonstrated superior efficacy compared with adalimumab and was well tolerated in patients with psoriasis through 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

64
779
7
29

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 727 publications
(918 citation statements)
references
References 39 publications
64
779
7
29
Order By: Relevance
“…77, 78 Both VOYAGE trials were 48-week studies that compared guselkumab to placebo and adalimumab, though the VOYAGE 2 trial also evaluated the clinical response in psoriasis patients with interrupted treatment (randomized withdrawal and retreatment). Results from the VOYAGE 1 and 2 trials were highly similar and reported a PASI90 response in 73% and 70% of patients, respectively, at week 16 compared to approximately 50% of patients treated with adalimumab.…”
Section: Recently Approved and Novel Therapeutic Agents For Psoriasismentioning
confidence: 99%
“…77, 78 Both VOYAGE trials were 48-week studies that compared guselkumab to placebo and adalimumab, though the VOYAGE 2 trial also evaluated the clinical response in psoriasis patients with interrupted treatment (randomized withdrawal and retreatment). Results from the VOYAGE 1 and 2 trials were highly similar and reported a PASI90 response in 73% and 70% of patients, respectively, at week 16 compared to approximately 50% of patients treated with adalimumab.…”
Section: Recently Approved and Novel Therapeutic Agents For Psoriasismentioning
confidence: 99%
“…For example, both IL-17A blockade with ixekizumab9 and IL-23 blockade with guselkumab36 are superior to TNF-α blockade (with etanercept and adalimumab, respectively). In other trials, IL-17A blockade with secukinumab,34 IL-17R blockade with brodalumab37 and IL-23p19 blockade with risankizumab38 all appear superior to IL-12/23p40 blockade with ustekinumab.…”
Section: The Th17 Axismentioning
confidence: 99%
“…The efficacy and safety of guselkumab were confirmed in three phase III trials in psoriasis: VOYAGE 1, VOYAGE 2 and NAVIGATE 14, 15, 16. Limited PSSD results from these studies have been reported previously.…”
Section: Introductionmentioning
confidence: 59%
“…3). 14 Greater proportions of patients in the guselkumab group achieved a score of 0 on each of the individual item scales for both the symptom and sign summary scores compared with placebo at week 16 (all P < 0.001) (Table 3). Similarly, greater proportions of patients in the guselkumab group achieved a score of 0 on each individual item scale for both symptoms and signs compared with adalimumab at weeks 24 and 48 (all P < 0.01) (Table 3).…”
Section: Resultsmentioning
confidence: 96%